2017
DOI: 10.1002/ase.1687
|View full text |Cite
|
Sign up to set email alerts
|

Using body donor demographics to assist the implementation of donation programs in Brazil

Abstract: The use of human material in anatomy education depends upon the generosity of body donors. However, little is known regarding the demographics of body donors in Brazil, where voluntary body donation is a relatively rare phenomenon. Hence, the aim of the present study was to elucidate the demographic profile of applicants to the Body Donation Program (BDP) at the Federal University of Health Sciences of Porto Alegre in Brazil, as well as to assess whether the observed characteristics of body donors are unique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
34
1
14

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 40 publications
9
34
1
14
Order By: Relevance
“…There appear to be many factors that could be taken into account when seeking potential body donors. Donors were found to be altruistic (Cornwall et al, ; da Rocha et al, ), co‐donate (if in a partnership; Anteby et al, ) and have long term partnerships (Cornwall et al, ). Cornwall () also suggests targeting registration of body donors to specific months of the year (Spring‐time; longer daylight hours) when a change in the neurochemistry of the brain occurs.…”
Section: Discussionmentioning
confidence: 99%
“…There appear to be many factors that could be taken into account when seeking potential body donors. Donors were found to be altruistic (Cornwall et al, ; da Rocha et al, ), co‐donate (if in a partnership; Anteby et al, ) and have long term partnerships (Cornwall et al, ). Cornwall () also suggests targeting registration of body donors to specific months of the year (Spring‐time; longer daylight hours) when a change in the neurochemistry of the brain occurs.…”
Section: Discussionmentioning
confidence: 99%
“…When prospective donors communicate such concerns, they tend to do so in rather vague, broad-brush ways. They say that they want to help mankind, society, the medical profession, or medical students and/or to make positive contributions to knowledge, science, medical research, or medical education and/or to 'avoid waste' (Fennell & Jones, 1992;Richardson & Hurwitz, 1995;Bolt et al, 2010;McClea & Stringer, 2010;Cornwall et al, 2012;da Rocha et al, 2017;Cornwall et al, 2018. See particularly the review included in Gürses et al, 2018).…”
Section: Issue 3 Identifying and Satisfying Donors' Desiresmentioning
confidence: 99%
“…In a recent study, [18] researchers stated that in order to maintain donation programs, it is essential first to understand the meaning of public opinion and then adopt strategies to improve donations. In addition, the same author suggested that donor profile surveys provide useful information about donors and the reasons they donate, which can be used to direct potential donors when setting donor programs, to circumvent difficulties in finding donors, or to monitor changes in donor profiles [18,19]. Body donation research shows that the identification of donor profiles facilitated campaigns aimed at informing the target population about voluntary donation of cadavers [19].…”
Section: Discussionmentioning
confidence: 99%